1998
DOI: 10.1080/07418829800093671
|View full text |Cite
|
Sign up to set email alerts
|

Explaining juveniles' attitudes toward the police

Abstract: Past studies of juveniles' attitudes toward the police suggest a single-cause model that implicates personal interactions with the police. We propose that attitudes toward authority and agents of social control develop in a larger, soc~iocuttural context. Specifically we hypothesize that juveniles' attitudes develop as a function of socialization in their communities' social environment, of their deviant subcultural '~preferences," and of the prior effect of these sociocultural factors on juveniles' contacts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
234
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(248 citation statements)
references
References 29 publications
11
234
3
Order By: Relevance
“…They must therefore assume that procedural justice affects-but is not affected by-legitimacy, and thus they almost certainly overestimate the effect of procedural justice. Other cross-sectional research, however, has found that the effects of youths' experience are mediated by community ties and delinquent subcultures (Brick et al 2009;Leiber et al 1998) The lessons that we take from the research on youths' attitudes toward the police are that trust in the police and other legal institutions, like political attitudes more generally, are to a large degree formed early in life, and while they are not immutable, early attitudes influence later attitude formation. They shape the experiences to which adolescents and young adults are exposed, and they form the lens through which those experiences are interpreted.…”
Section: Public Trust Of Police In Contextmentioning
confidence: 99%
“…They must therefore assume that procedural justice affects-but is not affected by-legitimacy, and thus they almost certainly overestimate the effect of procedural justice. Other cross-sectional research, however, has found that the effects of youths' experience are mediated by community ties and delinquent subcultures (Brick et al 2009;Leiber et al 1998) The lessons that we take from the research on youths' attitudes toward the police are that trust in the police and other legal institutions, like political attitudes more generally, are to a large degree formed early in life, and while they are not immutable, early attitudes influence later attitude formation. They shape the experiences to which adolescents and young adults are exposed, and they form the lens through which those experiences are interpreted.…”
Section: Public Trust Of Police In Contextmentioning
confidence: 99%
“…Compared to older-age groups, young people have greater contact with police officers, report more personal experience with mistreatment by officers, and hold more critical views of the police (Hurst, Frank, and Browning 2000;Leiber, Nalla, and Farnworth 1998). Gender is often insignificant by itself, but when examined in combination with age and race, it gains explanatory power.…”
Section: Explaining Citizen Perceptions Of the Police Individual Demomentioning
confidence: 99%
“…This pattern seems to be general and represents the best average description for all adolescents in the study, regardless of gender, race, or socioeconomic status. In other words, although the socio-cultural context, psychological factors, and peer-networks could be significantly influential in shaping youth's attitudes (Giordano, 1976;Leiber et al 1998), the issue of quality of treatment by authorities remains central to the reactions of juveniles (Hinds, 2007(Hinds, , 2009Crawford, 2009). Indeed, broader community factors may play a key role in the emergence of proactive aggression 7 (Fite et al 2009).…”
Section: The Issue Of Compliance To Authoritymentioning
confidence: 99%
“…Young people's extensive use of public space often attracts the attention and intervention of the police. From a subcultural perspective (Cohen, 1955;Cloward & Ohlin, 1960;Leiber et al 1998), adolescents exhibit negativity toward the police not necessarily because of negative experiences with it, but because they belong to a peer group that tends to reject authority altogether. Further, not abiding to the peer group's belief system places them at risk of rejection by peer group members.…”
Section: The Issue Of Compliance To Authoritymentioning
confidence: 99%